PENDEKATAN PEMBELAJARAN MODIFIKASI PERMAINAN SEBAGAI SOLUSI ALTERNATIF DALAM MENGEMBANGKAN GERAK DASAR MEMUKUL BOLA (STUDI DESKRIPTIF KUALITATIF PADA MAPEL PJOK DI KELAS TINGGI SEKOLAH DASAR KRAMAT PELA 09) - ulandari, wangi; Siregar, Rosinar; Sumantri, Syarif (Universitas Negeri Surabaya, 2024)
This research aims to identify the process of implementing a game modification learning approach as an alternative solution in developing basic movements of hitting the ball based on previous research. This research was conducted at SDN Kramat Pela 09 morning, Kebayoran Baru, South Jakarta. The research method used was descriptive qualitative research method. Data collection techniques using observation, interviews and documentation. Based on the research findings that researchers found in the field, 6 out of 10 students mentioned that they preferred the modified baseball game compared to the commonly used baseball. In addition, students also prefer the modified baseball game because the number of people in one team is less than the regular baseball game, it also makes the field used smaller so that students do not need to run as far as the regular baseball game. The game is also carried out with a smaller field area compared to the field in ordinary baseball. Keyword: Modification of Games; Development of Basic Movements; Hitting the Ball, Kasti Ball, PJOK.